A review of lifestyle and environment risk factors for pancreatic cancer. (March 2021) - Zanini, Sara; Renzi, Serena; Limongi, Antonina R.; Bellavite, Paolo; Giovinazzo, Francesco; Bermano, Giovanna
Abstract: Pancreatic cancer (PaCa) is one of the deadliest cancers known and its incidence is increasing in the developed countries. Because of the lack of biomarkers that allow early detection and the tendency of the disease to be asymptomatic, the diagnosis comes often too late for effective surgical or chemotherapy intervention. Lifestyle factors, that may cause common genetic modifications occurring in the disease, interfere with pancreatic physiology or function, and play a role in PaCa development, have been of concern recently, since a strategy to prevent this severe cancer is needed. This review identifies the latest evidences related to increased risk of developing PaCa due to dietary habits such as high alcohol, fructose and red or processed meat intake, and pathological conditions such as diabetes, obesity and infections in addition to stress and smoking behaviour. It aims to highlight the importance of intervening on modifiable risk factors: the action on these factors could prevent a considerable number of new cases of PaCa. Highlights: Smoking, high alcohol and red meat intake increase pancreatic cancer (PaCa) risk. Obesity and diabetes stimulate insulin production and predispose to onset of PaCa. Lifestyle and behaviour are linked with PaCa by plausible biological processes. Inflammation a potential common mechanism to lifestyle environment, diseases and PaCa.